High-toughness polylactic acid material, preparation method and film
By melt blending and extruding and blowing film forming of polylactic acid, polylactic acid copolymer, terminal hydroxyl epoxidation trans-1,4-polyisoprene and epoxy group chain extender, the problems of insufficient brittleness and strength of the polylactic acid film are solved, and the film strength and elongation of break are significantly improved.
Patent Information
- Application Number
- CN202411805757.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
Polylactic acid films have problems of brittleness and insufficient strength, which are difficult to meet existing usage requirements and performance requirements.
High strength and tough polylactic acid materials and films were prepared by melt blending and extruding and blown film forming of polylactic acid, polylactic acid copolymer, terminal hydroxyl epoxidation trans-1,4-polyisoprene and epoxy group chain extender.
The strength and elongation of break of polylactic acid film are significantly improved, the conduction of stress and the movement ability of PLA molecular chains are improved, and the mechanical properties of the film are enhanced.
Smart Images

Figure CN119708790A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polylactic acid films, in particular to a high-strength and tough polylactic acid material, a preparation method and a film. Background Art
[0002] Polylactic acid film is a new type of degradable packaging film. It uses plant resources as a substrate and is prepared by lactic acid polycondensation through biological fermentation. It has the characteristics of wide sources, green environmental protection and easy degradation. It has attracted much attention and plays an important role in the development direction of the packaging materials industry. However, polylactic acid film still has some disadvantages, such as greater brittleness and lower strength. In order to solve these problems, domestic and foreign researchers have conducted a lot of in-depth research on the compounding and physical property enhancement of polylactic acid film, and have achieved certain results. Some people doubled the molecular weight of PLA and found that its tensile modulus also doubled, while the tensile strength increased several times. This is because the film contains a higher content of L-type PLLA, resulting in higher tensile strength. The optical purity of PLLA is closely related to the performance of its products. The purity is about 60%, the melting point is 180℃, the glass transition temperature is 60℃, the tensile strength is higher than 60MPa, the tensile modulus is greater than 3GPa, and the elongation at break is about 3% to 6%, showing the characteristics of rigidity and brittle fracture. Miao Xiaoli and others used epoxidized eucommia gum to toughen the properties of modified polylactic acid, but used physical melt blending, which had poor compatibility, limited addition, and was difficult to produce two-dimensional materials such as films. It also restricted the mobility of molecular chains, and the tensile toughness was limited, and the strength was not high. People are in urgent need of a high-strength and tough polylactic acid material, preparation method, and film to meet existing usage needs and performance requirements. Summary of the invention
[0003] In view of the above problems, the present invention aims to provide a high-strength and tough polylactic acid material, a preparation method and a film.
[0004] The present invention is achieved through the following technical solutions: A high-strength and tough polylactic acid material is prepared from the following components: polylactic acid, a polylactic acid copolymer, terminal hydroxyl epoxidized trans-1,4-polyisoprene, and an epoxy group chain extender; wherein the weight of the polylactic acid copolymer is 5% to 10% of the weight of the polylactic acid, the weight of the terminal hydroxyl epoxidized trans-1,4-polyisoprene is 15% to 30% of the weight of the polylactic acid, and the weight of the epoxy group chain extender is 0.5% to 1.5% of the weight of the polylactic acid.
[0005] Furthermore, the terminal hydroxyl-epoxidized trans-1,4-polyisoprene is terminal hydroxyl-epoxidized synthetic eucommia rubber or terminal hydroxyl-epoxidized natural eucommia rubber.
[0006] Furthermore, the epoxy group chain extender is prepared by the following method: 16 to 17 parts of a solution with a mass volume concentration of 0.66 to 0.75 g / mL of 1,4-butanediol diglycidyl ether or 1,6-hexanediol glycidyl ether and ethyl acetate are prepared by volume, and the solution is added to a reactor, and the temperature is maintained at 20°C. Then, 7.6 parts of an ethyl acetate solution of diethylaminoethanol with a mass volume concentration of 0.46 g / mL is added to the reactor through a constant pressure dropping funnel, and the temperature is maintained at 25°C for 20 to 30 minutes of stirring and reaction. Under nitrogen protection, 40 parts of TDI isocyanurate and 20.00 parts of ethyl acetate are added to the reactor, and the temperature is raised to 50 to 60°C, and the reaction is continued for 40 to 60 minutes to obtain the product.
[0007] TDI isocyanurate is a TDI trimer polyisocyanate.
[0008] Furthermore, a method for preparing a high-strength and tough polylactic acid material comprises the following steps: (1) uniformly mixing dried polylactic acid, polylactic acid copolymer, terminal hydroxyl epoxidized trans-1,4-polyisoprene, and epoxy group chain extender, and obtaining a polylactic acid modified material by melt blending, extrusion, and drying; and (2) forming the polylactic acid modified material by film blowing to obtain a high-strength and tough polylactic acid film material.
[0009] Furthermore, in step (1), the melt blending extrusion is carried out in a twin-screw extruder, the temperature of the first extrusion zone is 165-175°C, and the temperatures of the second and third extrusion zones are 175-185°C.
[0010] Furthermore, in step (2), the film blowing is carried out on a single-screw film blowing machine, the screw diameter of the film blowing machine is 18 mm, the aspect ratio is 28:1, the die diameter is 40 mm, and the die gap is 0.6-1 mm; the 7 temperature intervals of the film blowing machine are set to 145°C, 160°C, 175°C, 180°C, 190°C, 195°C, and 210°C.
[0011] Furthermore, in step (2), during the film blowing, the blowing ratio is 3.0-3.5, and the stretching ratio is 3-4.
[0012] The film material is made of the above-mentioned high-strength and tough polylactic acid material.
[0013] Beneficial effects of the present invention: The invention discloses a high-strength and tough polylactic acid material, a preparation method and a film. The preparation method is simple and convenient. The raw materials are polylactic acid, a polylactic acid copolymer, terminal hydroxyl epoxidized trans-1,4-polyisoprene and an epoxy group chain extender. The epoxy group chain extender is prepared by reacting terminal hydroxyl epoxidized trans-1,4-polyisoprene, an oligomer containing both epoxy groups and terminal hydroxyl groups, and 1,4-butanediol diglycidyl ether or 1,6-hexanediol glycidyl ether with diethylaminoethanol and TDI isocyanurate. The epoxy group chain extender contains isocyanate and epoxy groups. In the process of melt blending and extrusion, polylactic acid, terminal hydroxyl epoxidized trans-1,4-polyisoprene and epoxy group chain extender can also undergo polycondensation and chain extension reaction, thereby improving the strength of the polylactic acid film. Strength; The addition of low molecular weight terminal hydroxyl epoxidized trans-1,4-polyisoprene can improve the mobility of PLA molecular chains and reduce the entanglement between chains. The flexible long-chain molecules of terminal hydroxyl epoxidized trans-1,4-polyisoprene are evenly dispersed in the system, acting as a bridge, which can well improve the conduction of stress. At the same time, it also makes the PLA molecular chains easier to move, plays a plasticizing role, and makes the PLA molecular chains easy to orient under the action of force, thereby improving performance. The epoxy group chain extender can cross-link the PLA molecular chains with the terminal hydroxyl epoxidized trans-1,4-polyisoprene molecular chains, exert the flexibility of the terminal hydroxyl epoxidized trans-1,4-polyisoprene molecular chains, and greatly improve the elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 (a) is the torque data of PLA modified material after adding different contents of terminal hydroxyl epoxidized trans-1,4-polyisoprene with 0.5% chain extender, (b) is the partial enlarged view of (a); Figure 2 The effect of chain extender on the rheological properties of the system; Figure 3 The tensile properties of PLA modified materials are shown in Figure 2 after adding 0.5% chain extender and adding different amounts of terminal hydroxyl epoxidized trans-1,4-polyisoprene. Figure 4 The effect of different chain extender contents on mechanical properties; Figure 5 Polarized light microscope photos of isothermal crystallization of terminal hydroxyl epoxidized trans-1,4-polyisoprene at 120°C (a) PLA; (b) PLA-0.5% expansion; (c) PLA-15% terminal hydroxyl epoxidized trans-1,4-polyisoprene; (d) PLA-30% terminal hydroxyl epoxidized trans-1,4-polyisoprene-0.5% expansion; Figure 6 The DSC second temperature rise curve of the blend of PLA / hydroxyl-terminated epoxidized trans-1,4-polyisoprene / chain extender; Figure 7 is the Vicat softening temperature data of the blend; Figure 8 The light transmittance of the film with 20wt% and 30wt% copolymer added is shown; Fig. 9 This is a real picture of the high-strength and tough polylactic acid film prepared by the present invention. DETAILED DESCRIPTION
[0015] The present invention is described below with specific examples, but is not intended to be limiting of the present invention.
[0016] The following equipment was used: micro twin-screw extruder: model GLZS-2, Wuhan Ruiming Testing Instrument Manufacturing Co., Ltd.; single-screw film blowing machine: model SY-6218-Z-18 / 28, Dongguan Shiyan Precision Instrument Co., Ltd. Example 1
[0017] A method for preparing a high-toughness polylactic acid film comprises the following steps: (1) Polylactic acid FY804 pellets dried to a moisture content of less than 0.4%, polylactic acid copolymer, terminal hydroxyl epoxidized trans-1,4-polyisoprene, and epoxy group chain extender were mixed uniformly, melt blended, extruded, and dried to obtain a polylactic acid modified material, wherein the weight of the polylactic acid copolymer was 5% of the weight of the polylactic acid, and the polylactic acid copolymer was purchased from Anhui Fengyuan Group Co., Ltd.; the weight of the terminal hydroxyl epoxidized trans-1,4-polyisoprene was 30% of the weight of the polylactic acid, and the weight of the epoxy group chain extender was 0.5% of the weight of the polylactic acid; the temperature of the first extrusion zone was 165°C, and the temperature of the second extrusion zone and the extrusion zone was 165°C. The temperature of the third zone is 175°C; the epoxy group chain extender is prepared by the following method: by volume, 16 parts of a solution with a mass volume concentration of 0.66 g / mL of XY622P Huizhou Xinyuan Technology 1,4-butanediol diglycidyl ether and ethyl acetate are prepared, and added to a reactor, the temperature is maintained at 20°C, and then 7.6 parts of an ethyl acetate solution of 0.46 g / mL diethylaminoethanol is added to the reactor through a constant pressure dropping funnel, and the reaction is maintained at 25°C for 20 minutes under stirring. Under nitrogen protection, 40 parts of Desmodur RC TDI isocyanurate and 20.00 parts of ethyl acetate are heated to 50°C and reacted for 40 minutes to obtain; (2) the polylactic acid modified material is subjected to film blowing to obtain a high-strength and tough polylactic acid film. The film blowing is carried out on a single-screw film blowing machine. The screw diameter of the film blowing machine is 18 mm, the aspect ratio is 28:1, the die diameter is 40 mm, and the die gap is 0.6 mm; the 7 temperature intervals of the film blowing machine are set to 145°C, 160°C, 175°C, 180°C, 190°C, 195°C, and 210°C. During film blowing, the blowing ratio is 3.0 and the stretching ratio is 3; the terminal hydroxyl epoxidized trans-1,4-polyisoprene is prepared by the following method: in a S212-100L stainless steel reactor, 10 parts of Belon EUGZP090 natural eucommia gum powder and 140 parts of toluene are added, by weight, and The mixture was dissolved by stirring at 55°C, 60 parts of clean water was slowly added dropwise and stirred for 1.5 hours, and then 6 parts of formic acid and 64 parts of 27.5% hydrogen peroxide were slowly added dropwise and stirred at 200rpm for 2 hours. After precipitation with anhydrous ethanol, the mixture was filtered and washed, and then washed with distilled water until neutral, and then dissolved with toluene to form a uniform glue solution with a solid content of 60%. 0.2 parts of sodium hypochlorite was added at 30°C under stirring at 200rpm, and the reaction was continued for 4 hours. After precipitation with anhydrous ethanol, the mixture was filtered and washed, and then dried at 40°C in vacuum for 48 hours to obtain a slightly transparent paste. A DMF (dimethylformamide) solution of 10% hydrazine hydrate in an amount of one-fourth of its mass was added to the paste. The mixture was continued to react for 5 hours under stirring at 55°C and 200rpm, and then precipitated with anhydrous ethanol, filtered and washed, and then dried at 40°C for 36 hours to obtain terminal hydroxyl epoxidized trans-1,4-polyisoprene. Example 2
[0018] A method for preparing a high-toughness polylactic acid film comprises the following steps: The polylactic acid FY804 dried to a moisture content of less than 0.3%, the polylactic acid copolymer, the terminal hydroxyl epoxidized trans-1,4-polyisoprene, and the epoxy group chain extender are uniformly mixed, melt blended, extruded, and dried to obtain a polylactic acid modified material, wherein the weight of the polylactic acid copolymer is 5% of the weight of the polylactic acid, and the polylactic acid copolymer is purchased from Anhui Fengyuan Group Co., Ltd.; the weight of the terminal hydroxyl epoxidized trans-1,4-polyisoprene is 15% of the weight of the polylactic acid, and the weight of the epoxy group chain extender is 1% of the weight of the polylactic acid; the temperature of the extrusion zone 1 is 175°C, and the temperature of the extrusion zone 2 and the extrusion zone 3 is 175°C. The temperature is 175°C; the epoxy group chain extender is prepared by the following method: by volume, XY622P Huizhou Xinyuan Technology 1,4-butanediol diglycidyl ether and ethyl acetate are prepared into a solution with a mass volume concentration of 0.66 g / mL, and added to a reactor, the temperature is maintained at 20°C, and then 7.6 parts of ethyl acetate solution of diethylaminoethanol with a mass volume concentration of 0.46 g / mL are added to the reactor through a constant pressure dropping funnel, and the reaction is maintained at 25°C for 30 minutes under stirring. Under nitrogen protection, 40 parts of Desmodur are added to the reactor. RCTDI isocyanurate and 20.00 parts of ethyl acetate are heated to 60°C and reacted for 60 minutes to obtain; (2) the polylactic acid modified material is subjected to film blowing to obtain a high-strength and tough polylactic acid film. The film blowing is carried out on a single-screw film blowing machine. The screw diameter of the film blowing machine is 18 mm, the aspect ratio is 28:1, the die diameter is 40 mm, and the die gap is 1 mm; the 7 temperature intervals of the film blowing machine are set to 145°C, 160°C, 175°C, 180°C, 190°C, 195°C, and 210°C. During film blowing, the blowing ratio is 3.5, the stretching ratio is 4, and the terminal hydroxyl epoxidized trans-1,4-polyisoprene is the same as in Example 1. Example 3
[0019] A method for preparing a high-toughness polylactic acid film comprises the following steps: The polylactic acid FY804 dried to a moisture content of less than 0.4%, the polylactic acid copolymer, the terminal hydroxyl epoxidized trans-1,4-polyisoprene, and the epoxy group chain extender are uniformly mixed, the weight of the polylactic acid copolymer is 10% of the weight of the polylactic acid, and the polylactic acid copolymer is purchased from Anhui Fengyuan Group Co., Ltd.; the weight of the terminal hydroxyl epoxidized trans-1,4-polyisoprene is 20% of the weight of the polylactic acid, and the weight of the epoxy group chain extender is 1.5% of the weight of the polylactic acid; the polylactic acid modified material is obtained by melt blending, extruding, and drying, and the temperature of the first extrusion zone is 170°C, and the temperature of the second extrusion zone and the extrusion zone is 100°C. The temperature of the third zone is 180°C; the epoxy group chain extender is prepared by the following method: by volume, XY632 Huizhou Xinyuan Technology 1,6-hexanediol glycidyl ether and ethyl acetate are prepared into a solution with a mass volume concentration of 0.75g / mL, 17 parts, added to the reactor, the temperature is maintained at 20°C, and then 7.6 parts of ethyl acetate solution of diethylaminoethanol with a mass volume concentration of 0.46g / mL are added to the reactor through a constant pressure dropping funnel, the reaction is maintained at 25°C and stirred for 25 minutes, and 40 parts of Desmodur are added to the reactor under nitrogen protection. RCTDI isocyanurate and 20.00 parts of ethyl acetate are heated to 55°C and reacted for 50 minutes to obtain a polylactic acid film. (2) The polylactic acid modified material is subjected to film blowing to obtain a high-strength and tough polylactic acid film. The film blowing is carried out on a single-screw film blowing machine. The screw diameter of the film blowing machine is 18 mm, the aspect ratio is 28:1, the die diameter is 40 mm, and the die gap is 0.8 mm. The 7 temperature intervals of the film blowing machine are set to 145°C, 160°C, 175°C, 180°C, 190°C, 195°C, and 210°C. During film blowing, the inflation ratio is 3.3 and the stretching ratio is 3.5.
[0020] The terminal hydroxyl epoxidized trans-1,4-polyisoprene is prepared by the following method: in a S212-100L stainless steel reactor, 10 parts of TPI-40 Shandong Dipai New Materials trans-1,4-polyisoprene and 140 parts of toluene are added by weight, stirred and dissolved at 55°C, 60 parts of clean water are slowly added dropwise and stirred for 1.5 hours, and then 6 parts of formic acid and 64 parts of 27.5% hydrogen peroxide are slowly added dropwise and stirred at 200rpm for 2 hours, and then precipitated with anhydrous ethanol, filtered, washed, and then washed with distilled water until neutral, and dissolved with toluene to form To a uniform glue solution with a solid content of 60%, 0.2 parts of sodium hypochlorite was added at 30°C under stirring at 200 rpm. The reaction was continued for 4 hours, and then precipitated with anhydrous ethanol, filtered, washed, and dried at 40°C in vacuum for 48 hours to obtain a slightly transparent paste. A 10% mass fraction of hydrazine hydrate in DMF (dimethylformamide) solution was added to the paste, and the reaction was continued for 5 hours under stirring at 55°C and 200 rpm. The solution was precipitated with anhydrous ethanol, filtered, washed, and dried at 40°C for 36 hours to obtain terminal hydroxyl epoxidized trans-1,4-polyisoprene.
[0021] Comparative Example 1 Compared with Example 2, this comparative example omitted the epoxy group chain extender in step (1), and the raw materials used in the remaining steps were the same.
[0022] Comparative Example 2 Compared with Example 1, in step (1), the epoxy group chain extender is replaced by a brand YMX-06 chain extender, and the raw materials used in the remaining steps are the same. Example 4
[0023] The addition of 0.5% of the chain extender containing epoxy groups was controlled, that is, compared with Example 1, the weight of the terminal hydroxyl epoxidized trans-1,4-polyisoprene used in step (1) of Example 1 was added at a ratio of 0%, 5%, 10%, 15%, and 20% relative to the weight of the polylactic acid, and the remaining steps were the same as Example 1. The PLA modified pellets were obtained in the same manner as Example 1 and tested. Example 5
[0024] The weight of the added terminal hydroxyl epoxidized trans-1,4-polyisoprene was controlled to be 15% of the weight of the polylactic acid, that is, compared with Example 2, the weight of the epoxy group chain extender used in step (1) of Example 2 was added at a ratio of 0.5% and 1.5% relative to the weight of the polylactic acid, and the remaining steps were the same as Example 2. The PLA modified material obtained in Comparative Example 1 and Example 2 was tested.
[0025] Note: Performance testing is carried out on the polylactic acid modified material and the polylactic acid modified material extrusion blown film products.
[0026] 1. Performance test of melt blending extrusion particles 1) Rheological properties test The melt properties of each PLA modified material in Example 1 and Example 4 were tested using an RM-200C extrusion torque rheometer. The temperatures of the three heating zones of the torque rheometer were set to 180°C, 180°C, and 180°C, the speed was set to 60r / min, and the sample weight was 50g each time. The results are shown in Table 1. Figure 1 As shown. Figure 1It can be seen that when the epoxy group chain extender is fixed, as the content of terminal hydroxyl epoxidized trans-1,4-polyisoprene increases, the torque is constantly decreasing at the same time when the curve is stable. This is because the addition of low molecular weight terminal hydroxyl epoxidized trans-1,4-polyisoprene can improve the mobility of PLA molecular chains and reduce the entanglement between chains, so the torque of the system is constantly decreasing, but the low torque data is not conducive to blown film processing. It means that the system is easier to flow in the molten state and difficult to form a film. Therefore, simply changing the amount of terminal hydroxyl epoxidized trans-1,4-polyisoprene cannot balance the blown film processing performance of PLA better, and a certain amount of epoxy chain extender needs to be added to improve the melt strength of the PLA modified material. After controlling the amount of terminal hydroxyl epoxidized trans-1,4-polyisoprene added unchanged, when the chain extender with different weight ratios of polylactic acid is added to polylactic acid alone, the melt properties of the melt-blended extruded particles of polylactic acid and chain extender are as follows: Figure 2 As shown, from Figure 2 It can be seen that with the continuous increase in the amount of chain extender added, the torque continues to increase at the same time. When the addition amount is 1.5%, the torque of the system is greatly improved. It can be seen that the addition of chain extender can improve the melt strength.
[0027] 2) Mechanical properties test Use a micro injection molding machine (SZS-15) to prepare the PLA modified materials in Example 1 and Example 4 into dumbbell-shaped specimens (tensile test). During injection molding, the barrel temperature of the micro injection molding machine is 190°C, the mold temperature is 45°C, and the injection and holding times are 7s and 15s, respectively. According to GB / T 1040.1-2018 Determination of tensile properties of plastics, the instrument used for tensile and bending tests is a microcomputer-controlled electronic universal testing machine (Sansi, UTM4013X), with a speed of 5mm / min. Five groups of each sample were tested and the average value was taken. The test results are as follows Figure 3 As shown in Table 1, Figure 3It can be seen that the addition amount of epoxy group chain extender is 0.5% unchanged. With the increase of the content of terminal hydroxyl epoxidized trans-1,4-polyisoprene, the elongation at break of the system is constantly increasing. Although the elongation at break of the system is not greatly improved when the addition amount is below 10%, the elongation at break can reach more than 280% after the addition amount reaches 15%, and the strength only decreases slightly. When the addition amount is 30%, the elongation at break is as high as 354%, which is 38 times higher than the original, while the strength only decreases by 37%. Such excellent performance is entirely due to the good compatibility of terminal hydroxyl epoxidized trans-1,4-polyisoprene and PLA. The flexible long-chain molecules of terminal hydroxyl epoxidized trans-1,4-polyisoprene are evenly dispersed in the system, acting as a bridge, which can well improve the conduction of stress. At the same time, it also makes the PLA molecular chain easier to move, plays a role of plasticization, and makes the PLA molecular chain easy to orient under the action of force, improving performance. When 5% of terminal hydroxyl-epoxidized trans-1,4-polyisoprene was added, the tensile strength was further improved compared with the 0% group. This was because terminal hydroxyl-epoxidized trans-1,4-polyisoprene acted as a nucleating agent, which improved the crystallization ability of PLA and led to an increase in tensile strength.
[0028] Table 1 Mechanical data of epoxidized trans-1,4-polyisoprene with different terminal hydroxyl contents
[0029] When epoxy group chain extenders are added to polylactic acid in different weight ratios, the tensile properties of the melt-blended extruded particles of polylactic acid and epoxy group chain extenders are as follows: Figure 4 As shown in the figure, it can be seen that the presence or absence of epoxy group chain extender has a huge impact on the elongation at break of the system, but further increasing the content of epoxy group chain extender has almost no effect on the tensile strength and elongation at break of the system. The reason may be that the epoxy group chain extender can react with the terminal hydroxyl epoxidized trans-1,4-polyisoprene end group, and its addition can link the PLA molecular chain with the terminal hydroxyl epoxidized trans-1,4-polyisoprene molecular chain, exerting the flexibility of the terminal hydroxyl epoxidized trans-1,4-polyisoprene molecular chain, and greatly improving the elongation at break. However, the number of end groups is limited, and the improvement of mechanical properties by continuing to add epoxy group chain extender becomes less obvious.
[0030] 3) Crystallinity analysis The spherulite morphology of the PLA modified materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 was observed using a polarizing microscope (MshotMP41) with a heating stage (MshotK3000). A glass slide was placed on the heating stage and fixed, and the sample was heated to 190°C. After melting, a cover glass was placed on the sample and pressed as thin as possible. The sample was kept at a constant temperature for 3 min, and then cooled to 120°C at a rate of 20°C / min. The temperature was maintained constant, and isothermal crystallization was observed under a polarizing microscope and the spherulite morphology was photographed from 0 to 10 min. The shooting time interval was 1 min. The results are shown in Figure 2. Figure 5 shown.
[0031] from Figure 5 It can be seen from the a1-a3 graphs in Figure 1 that when only PLA is contained, the PLA crystal grows slowly, and it takes 3 minutes for the crystal to almost fill half of the screen, and the spherulites are large in size. This well demonstrates the inherent disadvantages of PLA, which is slow crystallization and brittleness. Figure 5 As can be seen from the b1-b3 diagram in the figure, after adding 0.5% epoxy group chain extender, the system crystallization speed is greatly increased and it is almost full in about 2 minutes. This is because after the epoxy group chain extender reacts with the PLA end group, multiple PLA molecular chains are linked together, making it easier for the molecular chains to fold in the neighboring direction. The small crystals formed by the molecular chains that fold in the neighboring direction first and the unreacted epoxy group chain extender can also act as crystal nuclei to accelerate crystallization. Figure 5 As can be seen from Figure c1-c3, the crystallization rate of the system was greatly improved after adding only 15% of terminal hydroxyl epoxidized trans-1,4-polyisoprene. This is because the addition of terminal hydroxyl epoxidized trans-1,4-polyisoprene destroyed the close interaction between PLA molecular chains, improved the mobility of molecular chains, and made the neighbor folding of molecular chains easier to crystallize faster. Figure 5 It can be seen from the d1-d3 diagram that the crystallization ability decreases after adding 30% terminal hydroxyl epoxidized trans-1,4-polyisoprene. The reason is that terminal hydroxyl epoxidized trans-1,4-polyisoprene is an amorphous polymer. As the proportion of terminal hydroxyl epoxidized trans-1,4-polyisoprene increases, the crystallization ability of the system will have a trend of first increasing and then decreasing. When the content is low, it can improve the mobility of PLA molecular chains and accelerate crystallization. When the content is high, the distance between PLA molecular chains is increased, which hinders crystallization.
[0032] 4) DSC analysis DSC test was performed on each PLA modified material in Example 1, Example 4, and Comparative Example 1, as well as PLA and terminal hydroxyl epoxidized trans-1,4-polyisoprene. The instrument used was DSC Q2000. 10 mg of sample was placed in a crucible, placed in a heating furnace, the test software was opened, and the program was entered to start the test. The test program was to increase the temperature from 25 °C to 200 °C at a heating rate of 5 °C / min and keep it warm for 10 min. Then, the temperature was lowered to 25 °C at a cooling rate of 10 °C / min and kept warm for 10 min. The temperature was again increased from 25 °C to 200 °C at a heating rate of 5 °C / min, kept warm for 10 min, and then cooled to 25 °C at a rate of 10 °C / min. The heating and cooling curves in each program segment were recorded, and the second heating curve was used as the data for calculating the crystallinity of the material.
[0033] The crystallinity calculation of composite materials is shown in formula 1.1: Formula 1.1 Among them, Δ H m is the melting enthalpy of the second heating curve of the test sample, J / g; Δ H cc is the cold crystallization enthalpy of the second heating of the test sample, J / g; W f is the weight percentage of PLA in the sample, Δ H m0 is the ideal melting enthalpy of PLA when it is completely crystallized, which is 93.7 J / g.
[0034] The results are as follows Figure 6 As shown in Table 2, it can be seen from the figure that with the increase of temperature, pure PLA has an obvious glass transition platform, but no cold crystallization peak. The addition of terminal hydroxyl epoxidized trans-1,4-polyisoprene changes the T of PLA. g The higher the amount of terminal hydroxyl epoxidized trans-1,4-polyisoprene added, the higher the T g The lower the hydroxyl-terminated epoxidized trans-1,4-polyisoprene, the more mobility the PLA molecular chain has. cc The (cold crystallization temperature) is increasing, which means that the terminal hydroxyl epoxidized trans-1,4-polyisoprene destroys the regularity of the PLA molecular chain and inhibits its cold crystallization ability. At the same time, the crystallinity in Table 2 first increases and then decreases, which is basically consistent with the results observed under a polarizing microscope. The addition of a small amount of terminal hydroxyl epoxidized trans-1,4-polyisoprene is conducive to the crystallization of PLA, while the addition of a large amount of PLA will reduce the crystallization ability of PLA.
[0035] Table 2 Thermodynamic parameters of PLA / hydroxyl-terminated epoxidized trans-1,4-polyisoprene / epoxy chain extender blends
[0036] 5) Vicat softening temperature analysis The PLA raw materials and the PLA modified materials in Examples 1 and 4 were subjected to Vicat softening temperature analysis. The Vicat softening point temperature test (VST) is defined as the temperature at which the sample is subjected to a cross-sectional area of 1 mm 2 The temperature when the flat-end needle penetrates to a depth of 1 mm. The Vicat softening point temperature of the sample was measured using a Vicat softening point tester (XRW-300HB-6). The sample specifications were cylinders with a bottom diameter of 12 mm and a height of 5 mm. The parameter settings of the Vicat test refer to GB / T 1633-2000 Determination of Vicat softening temperature (VST) of thermoplastics. The medium was methyl silicone oil, the heating rate was 50°C / h, the load was 10 N, and the experiment was automatically stopped when the sample deformation reached 1 mm. Three groups of each sample were tested and the average value was taken.
[0037] The results are as follows Figure 7 As shown in the figure, a high Vicat softening temperature means that the material has better dimensional stability when heated and smaller thermal deformation. Figure 7 It can be seen that with the addition of terminal hydroxyl epoxidized trans-1,4-polyisoprene, the Vicat softening temperature of the blend is constantly decreasing, that is, the dimensional stability of the material is getting worse when heated, because terminal hydroxyl epoxidized trans-1,4-polyisoprene improves the chain movement ability of PLA, making it easier to move and deform when heated. This property is conducive to its application in the direction of heat shrinkable film.
[0038] 2. Mechanical properties and transmittance test of the film The tensile properties of the film were tested with reference to GB / T1040.3-2006 Determination of tensile properties of plastics Part 3: Test conditions for films and sheets. According to GB / T2918-2018, the temperature was 23°C, the adjustment time was 6h, the type 2 specimen was 15mm wide, the initial distance of the clamp was 50mm, and the tensile speed was 300mm / min.
[0039] Refer to GB / T 2410-2008 Determination of light transmittance and haze of transparent plastics. A haze meter (YH1200, Guangdong Sanenshi Intelligent Technology Co., Ltd.) was used to test the light transmittance of the film.
[0040] The test results are shown in Table 3.
[0041] Table 3 Tensile properties of films
[0042] The light transmittance of the high-toughness polylactic acid film prepared in Example 1 and Example 3 is shown as follows: Figure 8As shown. It can be seen that the films with 20wt% and 30wt% of terminal hydroxyl epoxidized trans-1,4-polyisoprene added have very good transparency. The haze meter detected that the transmittance of the 20wt% film was 90.25% and the haze was 34.37%; the transmittance of the 30wt% film was 90.37% and the haze was 35.23%. Both films have very good transmittance. The advantage of PLA transparency is well preserved. The good transmittance mechanism lies in the very good compatibility between PLA and terminal hydroxyl epoxidized trans-1,4-polyisoprene. Terminal hydroxyl epoxidized trans-1,4-polyisoprene can be evenly dispersed in PLA. At the same time, terminal hydroxyl epoxidized trans-1,4-polyisoprene itself is also an amorphous semi-transparent polymer, which has little effect on transparency.
[0043] The detailed description of the preparation method of a high-strength and tough polylactic acid film with reference to the above embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A high-strength polylactic acid material, characterized in that: The invention is prepared from the following components: polylactic acid, polylactic acid copolymer, terminal hydroxyl epoxidized trans-1,4-polyisoprene, and epoxy group chain extender; wherein the weight of the polylactic acid copolymer is 5% to 10% of the weight of the polylactic acid, the weight of the terminal hydroxyl epoxidized trans-1,4-polyisoprene is 15% to 30% of the weight of the polylactic acid, and the weight of the epoxy group chain extender is 0.5% to 1.5% of the weight of the polylactic acid.
2. The high-strength and tough polylactic acid material according to claim 1, characterized in that: The terminal hydroxyl epoxidized trans-1,4-polyisoprene is terminal hydroxyl epoxidized synthetic eucommia rubber and terminal hydroxyl epoxidized natural eucommia rubber.
3. The high-strength and tough polylactic acid material according to claim 1, characterized in that: The epoxy group chain extender is prepared by the following method: 16 to 17 parts of a solution with a mass volume concentration of 0.66 to 0.75 g / mL is prepared by mixing 1,4-butanediol diglycidyl ether or 1,6-hexanediol glycidyl ether with ethyl acetate by volume, and the solution is added into a reactor, and the temperature is maintained at 20° C. Then, 7.6 parts of an ethyl acetate solution with a mass volume concentration of 0.46 g / mL of diethylaminoethanol is added into the reactor through a constant pressure dropping funnel, and the temperature is maintained at 25° C. for stirring and reacting for 20 to 30 minutes. Under nitrogen protection, 40 parts of TDI isocyanurate and 20.00 parts of ethyl acetate are added into the reactor, and the temperature is raised to 50 to 60° C., and the reaction is continued for 40 to 60 minutes to obtain the epoxy group chain extender.
4. The high-strength and tough polylactic acid material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing dried polylactic acid, polylactic acid copolymer, terminal hydroxyl epoxidized trans-1,4-polyisoprene and epoxy group chain extender, and obtaining polylactic acid modified material by melt blending, extrusion and drying; and (2) forming the polylactic acid modified material by film blowing to obtain high-strength and tough polylactic acid film material.
5. The preparation method according to claim 4, characterized in that: In step (1), the melt blending extrusion is carried out in a twin-screw extruder, the temperature of the first extrusion zone is 165-175°C, and the temperatures of the second and third extrusion zones are 175-185°C.
6. The preparation method according to claim 4, characterized in that: In step (2), the film blowing molding is carried out on a single-screw film blowing machine, the screw diameter of the film blowing machine is 18 mm, the aspect ratio is 28:1, the die diameter is 40 mm, and the die gap is 0.6-1 mm; the 7 temperature intervals of the film blowing machine are set to 145°C, 160°C, 175°C, 180°C, 190°C, 195°C, and 210°C.
7. The preparation method according to claim 4, characterized in that: In step (2), during film blowing, the blowing ratio is 3.0-3.5, and the stretching ratio is 3-4.
8. A film material made of the high-strength and tough polylactic acid material described in any one of claims 1 to 3.
Citation Information
Cited By
Biodegradable film as well as preparation method and application thereof
CN121136362A
A biodegradable membrane, its preparation method and application
CN121136362B